Assessment on the right to healthy water: the way forward for sustainable future - Tagoranao, Mariam Saidano; Gamon, Alizaman Dumangcag; Wahyono, Zubaidi (APIUM, 2019)
Over the years, Malaysia has played a significant role in promoting the discourse on environmental sustainability both at the local and international forums. Towards realizing the principles and values that governed the vision for attaining the goals for a sustainable development, various policies were formulated by Malaysian government to redress societal expectations and aspirations in fulfilling the access to safe and clean water. Environmentalists have accord the priority of reductionist approach in knowing the nature of ecological crisis. This study attempts to explore Malaysia’s experience in implementing government policies on environmental sustainability and change - for the promotion of quality life through safe and clean water. The goal of the study is to assess and analyze government’s water vision in relation with the national water resources development plans. This research is very important because it assess the Federal Government intentions to have a uniform law on water service and supply to illustrate clearly the needs to balance development and sustainability in the country. The study relies on primary sources such as unpublished works and fieldwork in addition to library work. Reading materials relating to Malaysia’s vision on developing the country’s water resources will be consulted. In order to fulfill the goals of the study, the government efficiency in addressing the right to safe and clear water to all, including the environment will be evaluated. The study found out that Malaysian government was able to introduce new laws and policies that are consistent with international standards and strategies. It is therefore recommended that those provisions and policies, which are not consistent with the rights to clean and safe water must be amended. Equality and protection of rights should be given and enjoyed by all including the poor who are not financially capable to make a demand for clean and safe water. Keywords: rights to clean and safe water; assessment; sustainable development; Malaysia